(untitled) (Texas Journal of Philology, Culture and History, 2023)
the influence of the communicative space on the speech development of the individual is revealed. The main reason that creates a barrier to understanding the culture of speech among students is the deliberate distortion of the language, the language game, the use of slang, which leads to a closure in social, intellectual, and speech development.